2018
DOI: 10.20892/j.issn.2095-3941.2017.0173
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic flux response and glioblastoma sensitivity to radiation

Abstract: Objective:Glioblastoma is the most common primary brain tumor in adults and one of the most lethal human tumors. It constitutes a unique non-metastasizing human tumor model with high resistance to radiotherapy and chemotherapy. The current study investigates the association between autophagic flux and glioblastoma cell resistance.Methods:The expression kinetics of autophagy- and lysosome-related proteins following exposure of two glioblastoma cell lines (T98 and U87) to clinically relevant radiation doses was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Moreover, radiation preferentially activates autophagy in CD133 + cells and increases the levels of the autophagy-related proteins LC3, ATG5, and ATG12 [ 67 ]. The same was found in the radioresistant cell line, in which enhanced autophagic flux and silencing of the LC3A gene sensitized mouse xenografts to radiation [ 68 ]. However, in a study examining the induction of autophagy by radiation and its role in the radioresistance of GSCs, the authors found that GSCs expressed lower levels of autophagy-related protein LC3 and radiation induced a low degree of autophagy in these cells [ 69 ].…”
Section: Radioresistancementioning
confidence: 54%
“…Moreover, radiation preferentially activates autophagy in CD133 + cells and increases the levels of the autophagy-related proteins LC3, ATG5, and ATG12 [ 67 ]. The same was found in the radioresistant cell line, in which enhanced autophagic flux and silencing of the LC3A gene sensitized mouse xenografts to radiation [ 68 ]. However, in a study examining the induction of autophagy by radiation and its role in the radioresistance of GSCs, the authors found that GSCs expressed lower levels of autophagy-related protein LC3 and radiation induced a low degree of autophagy in these cells [ 69 ].…”
Section: Radioresistancementioning
confidence: 54%
“…There are a large number of investigations that show autophagy as a mechanism that confers protection against the induction of cell death by different antineoplastic agents [ 53 , 54 ], radiotherapy [ 55 ], or endocrine therapy in breast cancer [ 56 , 57 ] to mention a few examples. Despite the discussion, the role of autophagy in cancer is still debatable.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Autophagy plays a vital role in the malignancy, senescence, radioresistance, and chemoresistance of glioma. 30 32 It is therefore likely that LMX1B cooperates with NF-κB and E47 to regulate gankyrin expression in glioma patients, and upregulated gankyrin subsequently promotes the malignancy and poor prognosis of glioma by regulating autophagic flux. This hypothesis warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%